COMMUNICATION INTELLIGENCE : LEVERAGE YOUR STRENGTHS AND OPTIMIZE EVERY INTERACTION TO WORK BEST WITH OTHERS - Morgan, Claude D'Val (McGraw Hill, 2023)
The founder of The Forté Institute shares his time-tested assessment and proven strategies to help you build your communication strengths and develop Communication Intelligence (CQ) Now more than ever, Communication Intelligence is essential for workers at all levels. The good news is that you can learn to develop and master this vital competency. If you're interested in being your best through effective communication, that's exactly what you will find in the pages of Communication Intelligence.